Penerapan Media Crossword Lab Sebagai Inovasi Dalam Pembelajaran Al-Qur'an Hadist Di Ma Miftahul Jannah Kelas XII - Yuriska Amelia Putri; Ali Iskandar Zulkarnain (Jurnal Pengabdian Kepada Masyarakat, 2025)
This study aims to describe the application of Crossword Lab media as an innovation in learning the Qur'an Hadith in class XII MA Miftahul Jannah. The approach used is the Service Learning (SL) approach, which includes the stages of investigation, planning, implementation, and reflection, which are oriented towards increasing student interest, involvement, and creativity in an interactive and enjoyable way. Crossword Lab media is designed to help students understand the material actively through analytical and collaborative activities, so as to overcome obstacles such as boredom and lack of learning motivation. The results of the study show that the use of this media is able to increase student participation in the learning process, strengthen mastery of concepts, and motivate students to learn more meaningfully and enjoyably. In addition, the application of this method also helps in creating an innovative and interactive learning atmosphere, although it requires support from facilities and increased teacher competence to be optimal. In general, the application of Crossword Lab media has proven effective in improving learning outcomes and applicable and meaningful learning experiences in order to achieve student competencies as a whole